A new pattern of underground space‐time tridimensional gas drainage: A case study in Yuwu coal mine, China. Issue 2 (11th February 2019) - Li, Yankui; Wu, Shiyue; Nie, Baisheng; Ma, Yankun
Abstract: With the increase of mining depth, the high gassy coal mine confronts with a variety of gas problems, such as gas concentration exceeding the limit in the working face, gas outburst and gas explosion. According to the situation of gas drainage in Qinshui Basin (South of Shanxi Province, China) and enlightened by horizontal directional drillings (HDD) and multi‐branched horizontal wells, a new gas drainage pattern that inverted π ‐shape km borehole layout was proposed. Verified in Yuwu Coal Mine, the gas drainage data were standardized via the unified theory of standardization. It could dropped the coal seam gas content to 7.71 m 3 /t, and increased the gas drainage rate to 34.2%, which conformed to the Chinese regulation (<8 m 3 /t, >30%, respectively). This pattern has a significant effect on coal mines with a single seam, where protective seam mining technology was unsuitable to prevent gas outburst and gas explosion. Abstract : A double pressure relief circle model of gateway and borehole was proposed. Combined with traditional gas drainage technology, a new gas drainage scheme came up with – inverted π shape km boreholes group model. The novel gas drainage scheme of inverted π ‐shape km boreholes arrangement has the advantage of reducing gas drainage time and expanding coverage area. It is a new tri‐dimensional space‐time gas drainage system for underground coal mines.